Emoções e sentimentos na atuação docente: um estudo com professores de matemática na educação de jovens e adultos - Azevedo, Vera Lucia Antonio (2009)
This study aimed to emphasize the affective dimension as an important component to be considered in the understanding of teachers working in adult and youth education - EJA. Objective "understand the emotions and feelings involved in the teaching performance of teachers of Mathematics Education for Youth and Adults and provocative situations" questions: How did your start in teaching in EJA Course? Which were the affective aspects (feelings and emotions) that the entry and presence in the EJA Course you have? What are the most significant aspects in your performance in EJA as a teacher? To justify the relevance of research, surveys PRODEC to the production of theses and dissertations on the EJA. In the first chapter, it has been discussed "the field and the issue of adult and youth education." As the principal of the related theoretical work, in the second chapter, "the affective dimension in Wallonian theory" has been discussed. Then, it is presented the trajectory and methodological information about the interviews and diaries of ten teachers, five from a public institution and five from a particular institution. The information produced from the analysis of the interviews and diaries are presented in chapter four. Some issues are applied in the analysis: the teachers consider important the EJA Course, but realize that they have been started their activities without specific preparation for this, the importance of other people to help them in this new beginning of teaching was crucial, the care to teachers and students necessities guarantee feelings of well-being for both, and not care, feelings of malaise. As a result of the analysis, some suggestions are mentioned for training teachers of EJA Course